MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH DENGAN PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION - Damayanti Kusuma Wardhani; Wamington . Rajagukguk (Universitas Negeri Medan, 2015)
AbstractThis study aims to improve students' problem-solving abilities with STAD cooperative learning model on the subject of integers class VII SMP Negeri 3 Galang. This type of research is a classroom action research. The subjects were students of class VII-1 SMP Negeri 3 Assemble TA2014/2015 which amounted to28 students. The object of this study is an effort to improve the ability of mathematical problem solving through cooperative learning model Student Team Achievement Division(STAD) on the subject of Integer. The research instrument used is the observation and mathematical problem solving ability test. From the results of problem solving ability test, the data obtained were 9 students (32.14%), which reached the criteria of problem-solving abilities. After being given the treatment by applying the learning model STAD (first cycle), it is provided TKPMI .From the TKPMI data showed that as many as16students(57.14%) of the28students(2.74 value) that reaches criteria problem-solving abilities. This shows that in the first cycle of mathematical problem solving ability of students as a whole h as not reached 85%, the continued action on the second cycle. From the results TKPMII data showed that as many as 24 students (85.71%) of the 28 students (3.15 value) that reaches criteria problem-solving abilities. This shows that the mathematical problem solving ability of students as a whole has reached 85%, then the action is stopped. Based on t he above results, it can be concluded that by applying STAD cooperative learning model can improve students' mathematical problem solving ability on the subject of integers in class VII SMP Negeri 3Galang.Keywords: STAD, improve, test, problem, solving